APPLICABILITY OF NIC PRIORITY INTERVENTIONS FOR THE NURSING DIAGNOSIS INFFECTIVE AIRWAY CLARANCE - Anamaria Alves Napoleão; Emília Campos de Carvalho (Universidade Federal do Paraná, 2007)
This study aimed to identify the applicability of NIC priority interventions to the diagnosis ineffectiveAirway clearancein a pediatric intensive care unit (PICU), where the nursing process and NANDA's nursing diagnoses are adopted. The method usedwas the case study. The nurses spontaneously listed the activities they developed and analyzed whether they performed additionalactivities according to NIC taxonomy. The authors observed that in the PICU were performed 84.6% of the Respiratory Monitoringactivities, 80.0% of the Airway Management intervention activities and 36.4% of the activities regarding Cough Enhancementintervention. The conclusion was that the majority of the interventions studied are performed in the PICU and that NIC can give nursesthe opportunity to identify potentialities and needs as well as to improve the quality of the care delivered.